The Occurences of Heavy Mineral Placer at Kendawangan and Its Surrounding, West Kalimantan Province - Agus Setyanto; Maman Surachman (BULLETIN OF THE MARINE GEOLOGY, 2017)
The main objective of this study is to identify and to determine the variation and content of heavy mineral placer of Kendawangan coastal, offshore and its surrounding area. Sediment samples were taken from 18 locations, such as 12 samples from offshore and 6 samples from coastal area. For this analysis the heavy metals were identified and analyzed using isodynamic separator and binocular microscopic. The result indicates that heavy minerals consist of zircon, cassiterite, rutile, ilmenite, topaz, chalcopyrite, epidote, pyrite, hematite, hornblende and magnetite. Cassiterite and zircon are also found in sediment samples in all locations and potentially to be further developed. Keywords: Heavy minerals placer, Zircon, Cassiterite, Kendawangan, West Kalimantan Tujuan penelitian ini adalah untuk mengidentifikasi dan menentukan variasi kandungan mineral berat plaser pada sedimen pantai dan lepas pantai Kendawangan dan sekitarnya. Sampel sedimen diambil dari 18 lokasi yang terdiri atas 12 sampel sedimen lepas pantai dan 6 sampel sedimen pantai. Analisis dilakukan dengan menggunakan isodinamik separator dan mikroskop binokular. Hasil analisis menunjukkan bahwa mineral berat terdiri atas zircon, kasiterit, rutil, ilmenit, topas, kalkopirit, epidot, pirit, hematit, hornblende, dan magnetit. Kasiterit dan zircon juga dijumpai pada sampel sedimen di semua lokasi yang dianalisis dan berpotensi untuk dikembangkan lebih lanjut. Kata kunci: Mineral berat plaser, Zirkon, Kasiterit, Kendawangan, Kalimantan Barat